(untitled) (Quaderni di Gargnano, 2018)
The essay examines the corpus of Giovan Battista Marino’s known letters and, acknowledging how many letters have been lost, seeks to reconstruct the geographical and chronological distribution of the recipients. The second part includes close readings of several letters that are expressive Marino’s passion for works of art (drawings and paintings by early seventeenth-century artists) and several in which he passes judgment on the works of some contemporary poets.